28.7k views
2 votes
Simplify ((–3)^2)^3


A. (–3)^6
B. (3)^6
C. (3)^5
D. (–3)^5

User Mantler
by
6.4k points

2 Answers

6 votes


Use\ (a^n)^m=a^((n)(m))\\\\((-3)^2)^3=(3^2)^3=3^((2)(3))=3^6\\\\((-3)^2)^3=(-3)^((2)(3))=(-3)^6

Two answers: A. (-3)^6 and B. (3)^6.

But simplified is B. (3)^6

User Gabriel Reid
by
5.4k points
2 votes

Answer:

A and B

Explanation:

using the law of exponents


(a^m)^(n) =
a^(mn), hence


((-3)^2)^(3) =
(-3)^(6) → A

note that (- 3)² = 9 = 3², hence


(-3)^2)^(3) = (3²)³ =
(3)^(6) → B




User Viet Dinh
by
6.3k points